Toe flexor muscle strength in vocational ballet dancers: reliability, variability, and minimal detectable change of a custom-made dynamometer - Schrefl, A.; Schärli, A.; Goldmann, J.-P.; Erlacher, D.; Kolokythas, N. (Journal of Dance Medicine & Science, 2025)
Background: Toe flexor strength, which involves the combined activation of plantar intrinsic and extrinsic foot muscles, is crucial for locomotion, balance, and performance. Strong toe flexors are particularly crucial for efficient propulsion during running and jumping. Therefore, strengthening the feet has gained increased attention in the general population, as well as among athletes and dancers. However, accurately assessing foot muscle strength remains challenging. This study investigated the within- and between-session reliability of toe flexor maximal voluntary isometric contraction (MVIC) using a custom-made dynamometer.